2022
DOI: 10.2147/opth.s352731
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Changes in Choroid Vasculature Among Patients with Schizophrenia and Bipolar Disorder

Abstract: While structural changes within the retina of psychosis patients have been established, no detailed studies of choroidal microvasculature in these patients have been performed. Given evidence of microvascular disruption in psychosis patients, this study sought to determine whether there exists evidence of microvascular disruption in the choroids in these patients. Methods: Fifty-six subjects (20 controls and 36 psychosis patients) were recruited from April 2018 to February 2020. Five were excluded due to imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Li et al [9] 2022 No significant difference was observed in choroidal thickness in psychotic patients with healthy controls.…”
Section: Naghib Et Al [8] 2022mentioning
confidence: 92%
“…Li et al [9] 2022 No significant difference was observed in choroidal thickness in psychotic patients with healthy controls.…”
Section: Naghib Et Al [8] 2022mentioning
confidence: 92%
“…Adjusting for this metric is therefore recommended to minimize segmentation and atrophy biases, particularly in diseases with a neurodegenerative component. Several additional parameters have been identified as modulators of ChPs size: sex -the enlargement being greater in females in healthy controls, psychiatric disorders and pediatric MS [35,36 && ] -aging [37], adiposity and obesity [36 && ,38]. The pathophysiological correlates of ChP size changes in humans remain enigmatic and may involve various processes, including perfusion changes, inflammatory infiltrates, BCSFB dysfunction.…”
Section: Key Pointsmentioning
confidence: 99%
“…Adjusting for this metric is therefore recommended to minimize segmentation and atrophy biases, particularly in diseases with a neurodegenerative component. Several additional parameters have been identified as modulators of ChPs size: sex – the enlargement being greater in females in healthy controls, psychiatric disorders and pediatric MS [35,36 ▪▪ ] – aging [37], adiposity and obesity [36 ▪▪ ,38].…”
Section: In Vivo Analysis Of Choroid Plexuses In Human: the Imaging T...mentioning
confidence: 99%